Bridging worlds : emerging models and practices of U.S. academic libraries around the globe - Pun, Raymond, 1985-; Collard, Scott; Parrott, Justin (Association of College and Research Libraries, a division of the American Library Association, 2016)
Bridging Worlds: Emerging Models and Practices of U.S. Academic Libraries Around the Globe presents examples of libraries working to play their part in international campus development and engagement. This book provides practical best practices, lessons learned, and perspectives gained, from collection building to finances to designing spaces, and touches on some of the cultural, political, and social factors at play as institutions work to support these complex organizations.